2020
DOI: 10.1007/s40495-020-00243-4
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Chloroquine and Hydroxychloroquine on Skeletal Muscle: a Narrative Review

Abstract: Purpose of Review Concerning adverse neuromuscular effects, there are quite a few reports about the incidence and prevalence of chloroquine (CQ) and hydroxychloroquine (HCQ) myopathy. Given the above, I decided to explore the relationships of these drugs with skeletal muscle in an attempt to clarify how they affect the muscle now and in the future, as millions of people are using CQ and HCQ. Recent Findings The literature review identified 28 publications about CQ/HCQ m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
15
1
1
Order By: Relevance
“…Herein, we showed that longer exposure and higher cumulative doses are associated with higher disability and more common swallowing and cardiac involvement. Neuromuscular complications seem to be a late complication, as none of our patients and only very rare cases reported by others developed a myopathy with <6 months of exposure to CQ or HCQ ( 6 , 15 ). Hence, it would be less likely for a brief exposure to these drugs, such as when used during a viral infection, to cause a myopathy.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Herein, we showed that longer exposure and higher cumulative doses are associated with higher disability and more common swallowing and cardiac involvement. Neuromuscular complications seem to be a late complication, as none of our patients and only very rare cases reported by others developed a myopathy with <6 months of exposure to CQ or HCQ ( 6 , 15 ). Hence, it would be less likely for a brief exposure to these drugs, such as when used during a viral infection, to cause a myopathy.…”
Section: Discussioncontrasting
confidence: 41%
“…The clinical phenotype associated with CQ/HCQ myopathy has been mainly described in the literature as a proximal myopathy ( 5 , 8 , 15 ). In this study, we demonstrate that CQ/HCQ myopathy is associated with a wide spectrum of clinical presentations consisting of one or a combination of the following: proximal limb, swallowing, respiratory, and axial muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From remdesivir, ritonavir, and lopinavir it is known that they occasionally trigger rhabdomyolysis ( Ghasemiyeh et al, 2020 ). From chloroquine it is well known that it may cause toxic myopathy ( Carvalho, 2020 ). Known side effects of tocilizumab include arterial hypertension, hyperlipidemia, obesity, infections, bowel ulceration, and heart failure ( Saito et al, 2020 ), which may secondarily cause cerebrovascular disease.…”
mentioning
confidence: 99%
“… 3 From chloroquine it is known that it can be myotoxic and can cause permanent myopathy. 4 Steroids can induce mitochondrial myopathy. Tocilizumab has been reported to occasionally induce myositis.…”
mentioning
confidence: 99%